The main tendencies of the current reform of the Ukrainian legislation in the field of health care - M. A. Anishchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The purpose of the research – to study the basic development directions of the legislation of Ukraine in the field of health care, to identify problems of reformation of the above legislation, to outline ways of their solution.